The Tradition of the Legacy of ‘Look Malu’ in Timor-Leste Society: An Ecolinguistic Study (e-Journal of Linguistics, 2025)
The study of the tradition of 'look malu' or presenting betel nut in Timor society, is one part of the study that correlates with ecoculture in the context of Ecolinguistics with the aim of identifying, exploring, and arranging in a series of visual data for analysis. This study was realized based on the theory of text data studies from Creswell (2009) in Sugiyono (2012: 14) and data analysis methods from Maxwell & Chamiel (2014) in Ascarya Academia (2021). The tradition of 'look malu' that applies in the social relations of community life has several functions that are concretely appreciated in the social life of the supporting community that runs from time to time.